The Implementation of Flipped Learning Approach with A Guided Inquiry Model to Science Process Skills & Chemical Literacy on Reaction Rate Material - Tonapa, Nely; Atun, Sri (Jurnal Penelitian Pendidikan IPA, 2024)
This study investigates the impact of a flipped learning approach combined with a guided inquiry model on students' science process skills and chemical literacy in reaction rate material. The quasi-experimental research employed a non-equivalent pretest-posttest control group design with 71 eleventh-grade high school students as participants. Instruments included a chemical literacy test and a science process skills observation sheet. Data analysis using MANOVA revealed significant differences and effects between the guided inquiry-flipped learning and discovery learning models, with an effective contribution of 29.70%. These findings highlight the positive influence of the guided inquiry and flipped learning approach on enhancing science process skills and chemical literacy.